360° Virtual reality to improve patient education and reduce anxiety towards atrial fibrillation ablation - Hermans, Astrid N L; Betz, Konstanze; Verhaert, Dominique V M; den Uijl, Dennis W; Clerx, Kristof; Debie, Luuk; Lahaije, Marion; Vernooy, Kevin; Linz, Dominik; Weijs, Bob (Europace (London, England), 2023)
Abstract Aims Evaluation of (i) the effects of a virtual reality (VR) preprocedural patient education video on information provision, procedure-related knowledge, satisfaction, and the level of worries in patients planned for atrial fibrillation (AF) ablation and (ii) the feasibility of a disposable cardboard VR viewer for home use in this setting. Methods and results In this prospective observational cohort study, patients were alternatively assigned in a 1:1 ratio to the control or VR group. Controls received standard preprocedural information. VR group received standard information and a VR video (via in-hospital VR headset and disposable cardboard). The Amsterdam Preoperative Anxiety and Information Scale (APAIS) together with additional questions concerning procedural experience and satisfaction was completed pre- and post-ablation. Of 134 patients [38.1% female, aged 66 (58–72) years] included, 49.2% were assigned to the control and 50.7% to the VR group. The number of patients that worried about the ablation procedure was lower in VR than in control patients (19.1% vs. 40.9%, P = 0.006). More VR females than males had worries about the procedure (34.8% vs. 11.1%, P = 0.026). The number of VR patients that were satisfied with the preprocedural information provision was higher post-ablation than pre-ablation (83.3% vs. 60.4%, P = 0.007). In total, 59.4% reported that the disposable cardboard was easy to use and led to a discussion with relatives in 68.8%. Conclusion In patients scheduled for AF ablation, a VR preprocedural educational video led to better information provision and procedure-related knowledge, higher satisfaction, and less worries regarding the procedure. The disposable cardboard was feasible for home use.